Small vertical movement of a K+ channel voltage sensor measured with luminescence energy transfer - Posson, David J.; Ge, Pinghua; Miller, Christopher; Bezanilla, Francisco; Selvin, Paul R. (Nature (London), 2005)
Voltage-gated ion channels open and close in response to voltage changes across electrically excitable cell membranes 1 . Voltage-gated potassium (Kv) channels are homotetramers with each subunit constructed from six transmembrane segments, S1–S6 (ref. 2 ). The voltage-sensing domain (segments S1–S4) contains charged arginine residues on S4 that move across the membrane electric field 2 , 3 , modulating channel open probability. Understanding the physical movements of this voltage sensor is of fundamental importance and is the subject of controversy. Recently, the crystal structure of the KvAP 4 channel motivated an unconventional ‘paddle model’ of S4 charge movement, indicating that the segments S3b and S4 might move as a unit through the lipid bilayer with a large (15–20-Å) transmembrane displacement 5 . Here we show that the voltage-sensor segments do not undergo significant transmembrane translation. We tested the movement of these segments in functional Shaker K + channels by using luminescence resonance energy transfer to measure distances between the voltage sensors and a pore-bound scorpion toxin. Our results are consistent with a 2-Å vertical displacement of S4, not the large excursion predicted by the paddle model. This small movement supports an alternative model in which the protein shapes the electric field profile, focusing it across a narrow region of S4 (ref. 6 ).